Apple Inc. and the U.S.–China Tariff War: Identifying, Assessing, and Mitigating Risks - Putra, Abhiyoga Deyandra; Ardanesworo, Muhammad Feyzel Khalfani Putra; Rukmana, Ovalia (CV. Ulil Albab Corp, 2025)
This study examines Apple Inc.’s mitigation strategies amid escalating U.S.–China tariff tensions. Using ISO 31000, COSO ERM, and the Four T Model, key risks are assessed through a probability–severity matrix and heatmap based on Apple’s 2024 Annual Report and industrial data. The analysis reveals that diversification efforts to India and Vietnam remain symbolic, as Apple’s core dependencies—such as final assembly and chip fabrication—persist in high-risk regions like China and Taiwan. Financial hedging and supplier shifts show partial effectiveness but fail to address long-term geopolitical volatility. Comparisons with Samsung and Google demonstrate Apple’s relative rigidity in adapting supply chain strategies. Findings suggest the need for deeper structural reforms emphasizing proactive geopolitical forecasting and ESG-integrated vendor governance to build enduring resilience.